Osteoid-osteoma and osteoblastoma with rare localization – presentation of 4 clinical cases - Kircho Patrikov; Yordan Ivanov (Journal of the Bulgarian Orthopaedics and Trauma Association)
Osteoid-osteoma and osteoblastoma are the two most common representatives of benign bone-forming tumors. Although both tumors are well known to the orthopedic community in Bulgaria, there are several rare localizations that would present difficulties in the diagnostic and therapeutic process. The purpose of our report is to present 4 pediatric cases with rare localization of osteoid-osteoma and osteoblastoma, diagnosed and treated in our clinic in the period between 2020-2022. The presented rare localizations of osteoid-osteoma and osteoblastoma may lead to a delay in making the correct diagnosis. Often, such patients are treated for long periods of time without much effect, which can lead to a deterioration in their quality of life.